THE POSITIVE INFLUENCE OF IMPLEMENTING PROJECT TO STRENGTHENING PANCASILA STUDENT PROFILE (P5) WITH A THEME OF ENGINEERING AND TECHNOLOGY TO BUILD UNITARY STATE OF REPUBLIC OF INDONESIA FOR GRADE IV STUDENTS AT INTI NUSANTARA TEBING TINGGI PRIVATE ELEMENT - Ridwan Syahputra (Sean Institute, 2023)
The Project to Strengthen Pancasila Student Profile (P5) is an effort to support the achievement of the Pancasila Student Profile by using a new understanding through project-based learning. By implementing P5, teachers are expected to be able to carry out their role optimally in a lesson and accompany the student learning process so that they can grow capacity and build good character and make students the successors of a superior and productive nation. Develop competence as educators who are open to collaborating with educators from other subjects to enrich learning outcomes. This study aims to determine the mastery of the Pancasila Student Profile Strengthening Project (P5). The sample of this research was fourth grade students at Inti Nusantara Tebing Tinggi Private Elementary School for the academic year 2023 - 2024. This study aims to see the positive effects of the Pancasila Student Profile Strengthening Project (P5) with the theme Engineering and Technology to build the Unitary State of the Republic of Indonesia for grade IV students at Inti Nusantara Private Elementary Schools High cliff.